2022
DOI: 10.3390/en15113983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Particle Size Reduction and Fe3O4 Additives on Biogas and Methane Yields of Arachis hypogea Shells at Mesophilic Temperature

Abstract: Enzymatic hydrolysis of lignocellulose materials has been identified as the rate-limiting step during anaerobic digestion. The application of pretreatment techniques can influence the biodegradability of lignocellulose substrate. This study combined Fe3O4 nanoparticles, which serve as a heterogeneous catalyst during anaerobic digestion, with different particle sizes of Arachis hypogea shells. Batch anaerobic digestion was set up at mesophilic temperature for 35 days. The results showed that 20 mg/L Fe3O4 addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…A 178% increase in methane yield released was reported when acidic pretreatment of groundnut shells was considered . It can be observed that among some of the pretreatment techniques experimented with on groundnut shells, DES pretreatment produced the most significant improvement except when combined pretreatment (particle size reduction and Fe 3 O 4 additive) was investigated (Olatunji et al, 2022b). However, it has been reported that combined pretreatment increases the cost of production compared to single pretreatment, which could present DES pretreatment as the most efficient method.…”
Section: Figurementioning
confidence: 99%
“…A 178% increase in methane yield released was reported when acidic pretreatment of groundnut shells was considered . It can be observed that among some of the pretreatment techniques experimented with on groundnut shells, DES pretreatment produced the most significant improvement except when combined pretreatment (particle size reduction and Fe 3 O 4 additive) was investigated (Olatunji et al, 2022b). However, it has been reported that combined pretreatment increases the cost of production compared to single pretreatment, which could present DES pretreatment as the most efficient method.…”
Section: Figurementioning
confidence: 99%
“…Lignocellulosic materials' size reduction during milling pretreatment increased the anaerobic digestion's capacity to buffer, which helps to reduce the acidity of AD. The substrate's particle sizes have an immediate impact on digestion since they immediately correlate with the amount of hydrolysing enzyme surface area that is accessible [ 85 , 86 ].…”
Section: Factors Affecting Biogas Production From Algaementioning
confidence: 99%
“…45 The recent development in multidisciplinary research has reported the application of nanoparticles, natural deep eutectic solvents (NADES), deep eutectic solvents (DES), and ionic liquids for feedstock pretreatments as a new novel means of pretreating biogas feedstocks. [55][56][57] Despite the successes recorded in the feedstock pretreatment, some demerits were observed. This includes the high energy inputs, particularly for thermal and mechanical methods, the release of inhibitory materials and corrosion/environmental challenges associated with a chemical pretreatment, the release of inhibitory compounds that lower the digestion rate, and the exorbitant cost of enzymes for biological pretreatments.…”
Section: Anaerobic Digestion Of Macroalgaementioning
confidence: 99%
“…The alteration of the pH beyond the acceptable range (6–8) was harmful to the methanogenic bacteria activities and reduced the gas yield. 55,73 It was discovered that the majority of the algae biological pretreatments were focused on microalgae pretreatment. The few works of literature accessed were mainly on the application of fungi and enzymes.…”
Section: Macroalgae Pretreatmentmentioning
confidence: 99%
See 1 more Smart Citation